IFN-γ activated JAK1 shifts CD40-induced cytokine profiles in human antigen-presenting cells toward high IL-12p70 and low IL-10 production - Conzelmann, Michael; Wagner, Andreas H.; Hildebrandt, Anke; Rodionova, Elena; Hess, Michael; Zota, Annika; Giese, Thomas; Falk, Christine Susanne; Ho, Anthony Dick; Dreger, Peter; Hecker, Markus; Luft, Thomas (Biochemical pharmacology, 2010)
CD40Ligand (CD40L) represents a strong endogenous danger signal associated with chronic inflammatory disease. CD40L induces activation of antigen-presenting cells (APCs) such as DCs, monocytes, B-cells and endothelial cells. However, CD40 activation alone, whilst inducing IL-10 production, is insufficient to induce interleukin (IL)-12p70 release in human APCs suggesting that additional cytokine signals (e.g. GM-CSF, IL-4 or IFN-γ) are required for the induction of a pro-inflammatory cytokine profile. We demonstrate that IFN-γ-induced Janus kinase 1 (JAK1) enhances CD40-induced IL-12p70 release whilst simultaneously inhibiting IL-10 synthesis, resulting in a pro-inflammatory phenotype of CD40L-activated dendritic cells (DCs). JAK2 mediated enhancing effects on IL-12p70 but did not inhibit IL-10 release, whereas Tyk2 mediated inhibitory effects on IL-12p70 release in this system. The mechanism by which complementary IFN-γ/JAK activities affect IL-12p70 production involves STAT1 activation and de novo induction of interferon-responsive factors (IRF)-1 and IRF-8. Simultaneously, JAK1 was unique in inhibiting IL-10 synthesis via STAT1 and IRF-8 with both transcription factors binding to the IL-10 promoter. We demonstrate that CD40- and JAK/STAT/IRF-signalling pathways are strictly complementary for the induction of a pro-inflammatory cytokine profile in human APCs. This suggests that a number of CD40 effects in chronic inflammatory diseases might be weakened by targeting JAK/STAT.